Adapting extracellular matrix proteomics for clinical studies on cardiac remodeling post-myocardial infarction. Issue 1 (December 2016) - Lindsey, Merry; Hall, Michael; Harmancey, Romain; Ma, Yonggang
Abstract Following myocardial infarction (MI), the left ventricle (LV) undergoes a series of cardiac wound healing responses that involve stimulation of robust inflammation to clear necrotic myocytes and tissue debris and induction of extracellular matrix (ECM) protein synthesis to generate a scar. Proteomic strategies provide us with a means to index the ECM proteins expressed in the LV, quantify amounts, determine functions, and explore interactions. This review will focus on the efforts taken in the proteomics research field that have expanded our understanding of post-MI LV remodeling, concentrating on the strengths and limitations of different proteomic approaches to glean information that is specific to ECM turnover in the post-MI setting. We will discuss how recent advances in sample preparation and labeling protocols increase our successes at detecting components of the cardiac ECM proteome. We will summarize how proteomic approaches, focusing on the ECM compartment, have progressed over time to current gel-free methods using decellularized fractions or labeling strategies that will be useful for clinical applications. This review will provide an overview of how cardiac ECM proteomics has evolved over the last decade and will provide insight into future directions that will drive forward our understanding of cardiac ECM turnover in the post-MI LV.